(untitled) (European Journal of Pure and Applied Mathematics, 2024)
The idea of Lukasiewicz t-norm is used to construct the concept of ε-Lukasiewicz fuzzy sets based on a given fuzzy set. The ε-Lukasiewicz fuzzy sets are applied to UP (BCC)-algebras. Moreover, the notion of ε-Lukasiewicz fuzzy UP (BCC)-subalgebras is introduced, and its various properties are investigated. Three subsets, so-called -set, q-set, and O-set, are constructed, and the conditions under which they can be UP (BCC)-subalgebras are explored.